1999
DOI: 10.1038/sj.bjc.6690062
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drug-induced apoptosis in gastric cancer cells is blocked by protein kinase C activation through inhibition of c-myc

Abstract: Summary Apoptosis plays a major role in gastrointestinal epithelial cell turnover, ulcerogenesis and tumorigenesis. We have examined apoptosis induction by non-steroidal anti-inflammatory drugs (NSAIDs) in human gastric (AGS) cancer cells and the role of protein kinase C (PKC) and apoptosis-related oncogenes. After treatment with aspirin or indomethacin, cell growth was quantified by MTT assay, and apoptosis was determined by acridine orange staining, DNA fragmentation and flow cytometry. The mRNA and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…Another group demonstrated that a PKCb inhibitor exhibited anti-angiogenic and anti-tumor effects in human gastric cancer xenografts (Teicher et al, 2001b). Previously, our group have reported that PKC inhibitors induced apoptosis in human gastric cancer cell lines through modulating apoptosis-related genes (Zhu et al, 1999a) and activation of PKC by the phorbol ester 12-0-tetradecanoylphorbol-13-acetate (TPA) inhibited the apoptosis induced by indomethacin in gastric cancer cells, accompanied by the upregulation of expression of p21 waf1/cip1 and downregulation of c-myc (Zhu et al, 1999b). Besides, we also demonstrated that overexpression of PKCb 1 suppressed indomethacin-induced apoptosis in gastric cancer cells through the up-regulation of p21 waf1/cip1 (Zhu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Another group demonstrated that a PKCb inhibitor exhibited anti-angiogenic and anti-tumor effects in human gastric cancer xenografts (Teicher et al, 2001b). Previously, our group have reported that PKC inhibitors induced apoptosis in human gastric cancer cell lines through modulating apoptosis-related genes (Zhu et al, 1999a) and activation of PKC by the phorbol ester 12-0-tetradecanoylphorbol-13-acetate (TPA) inhibited the apoptosis induced by indomethacin in gastric cancer cells, accompanied by the upregulation of expression of p21 waf1/cip1 and downregulation of c-myc (Zhu et al, 1999b). Besides, we also demonstrated that overexpression of PKCb 1 suppressed indomethacin-induced apoptosis in gastric cancer cells through the up-regulation of p21 waf1/cip1 (Zhu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…11 However, most in vitro studies have shown that induction of apoptosis by NSAIDs and selective COX-2 inhibitors is COX-2 dependent. 8,[12][13][14][15][16][17] Inhibition of angiogenesis also plays a role in the chemoprevention of COX-inhibitors. Expression of COX-2 is found to be associated with VEGF expression and microvessel density (MVD) in gastric cancer, [18][19][20][21] and NSAIDs were found to inhibit in vitro angiogenesis of human microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Like apoptosis, proliferation and differentiation are regulated by genes. C-myc is an important gene involved in the control of cell proliferation, and could up-regulate cell cycle progression, and induce cell proliferation [26][27][28][29] . C-fos gene is considered as an early response gene, and its expression level was in proportion to the differentiation degree of gastric cancer [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%